Effects of Thyrotoxicosis on the Structure of Salivary Glands (Submandibular Glands) in Swiss Albino Mice (Mus musculus) - Alkasiy, K. S.; Al-Habib, M.F.; Sabrei, D. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The goal of this study  was intend to study the effects of inducedthyrotoxicosis on the histological structure of submandibular gland.Two groups of mature albino mice wen: used, the first group was injected (subcutaneous) daily  with  (0.2_0.4)ml  norma] salinfor 11 days and used as control group, while the second group was injected daily wi th L_thyroxin (T4) 0.2mg /Kg (subcutaneous) for l l days.At  the  end  of   the  treatment  , supmandibular  glands      were processed for light microscopic examination .The result.s have shown the   presence of degenertaive changes of major submandibular acini cells in animal treated with thyroxin with diminishing amounts of  connective tissuelements .   Beside these change infiltration with inflammatory cells were observed . From this study we can conclude that there is a relationship between  thyroid gland and submandibular gland . Which might  regulated the secretory activity of saliva .